Developing Web-Based Patient Reservation and Data Management System using Rapid Application Design - Subiyakto, A'ang; Yudhanta, Satya; Aini, Qurrotul (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
A private infant and toddler care clinic in the South Tangerang area, Omah Bayi, faces problems in managing reservations and patient data. During this time, reservations were recorded in a book and scheduling was done verbally. This causes inefficiency and increases the possibility of data recording errors. To solve this problem, a web-based reservation system was developed using the rapid application development (RAD) method. This method involves requirements analysis, design, implementation, and system testing, with the support of technologies such as PHP and MySQL. The designed system effectively shortens the turnaround time of the reservation process and patient data management. Test results show that reservation recording time is reduced from 10 minutes to two minutes (80% faster), and monthly report preparation time is reduced from two hours to 10 minutes (92% faster). This research aimed to create a digital solution that will not only improve the clinic's operational efficiency and prevent data duplication but will also make services more accessible to patients. It is expected that the implementation of this system will be the first step towards the clinic's digital transformation and will have a positive impact on the development of healthcare services in the future.